(untitled) (TAJ: Journal of Teachers Association, 2023)
Background: Serum cholinesterase mainly comes from the liver, a sensitive indicator of the synthetic capacity of the liver. It can be used as a prognostic marker for cirrhosis. Objectives: To measure the serum cholinesterase level in cirrhotic patients and to correlate its level with the severity of the disease as per the Child-Pugh score. Methodology: This cross-sectional study was conducted in the Department of Gastroenterology, Sir Salimullah Medical College Mitford Hospital, Dhaka, Bangladesh, from January 2018 to December 2018. Fifty adult patients with cirrhosis of the liver were enrolled. Fifty healthy individuals were also taken to compare serum cholinesterase levels. Cirrhotic patients were grouped strictly into A, B, and C classes, as per the Child-Pugh score. Serum cholinesterase level was measured in all participants. The correlation between cholinesterase level and the severity of the disease was analyzed. Result: Mean age of the patients was 47.42 ± 12.40 years and 47.22 ± 11.99 years in cirrhotic patients and healthy group, respectively. The number of patients in the Child-Pugh A, B, and C subgroups was 12 (24%), 20 (40%), and 18 (36%), respectively. The mean serum cholinesterase level was 2938 ± 1561 U/L in cirrhotic patients and 9036 ± 2024 U/L in the healthy group. Serum cholinesterase level in different Child-Pugh class was 4740 ± 1046 U/l (Child A), 3157 ± 1161 U/l (Child B), and 1493 ± 500 U/l (Child C). Serum Cholinesterase was positively correlated with serum albumin and negatively correlated with bilirubin, prothrombin time, and INR. A negative correlation was found between serum Cholinesterase level and the severity of the disease. Conclusion: Serum cholinesterase level was low in cirrhotic patients, and its level was inversely correlated with the severity of the disease. Thus it can be used as a prognostic marker of cirrhosis. However, further study with a large sample size could explain this more precisely. TAJ 2022; 36: No-1: 33-40